PENAFSIRAN AYAT TAHARAH SURAH AL-MAIDAH AYAT6 DAN AN-NISA AYAT 43 - Muhayat Musa (Makkah: Journal Of Islamic Studies, 2025)
This study examines the interpretation of purification (taharah) verses in the Qur’an, specifically Surah an-Nisa’ verse 43 and Surah al-Ma’idah verse 6, which constitute the fundamental textual basis for Islamic jurisprudence on ritual purity. The scope of this research focuses on the interpretation of these verses by classical and contemporary mufassirs and their implications for Islamic legal rulings related to wudu’, ghusl, and tayammum. The objective of this study is to analyze the similarities and differences in the exegetical approaches to both verses and to identify their contributions to the formulation of fiqh al-taharah. This research employs a qualitative library research method using a descriptive-analytical approach, drawing on primary sources of Qur’anic exegesis and fiqh literature. The findings indicate that QS. al-Ma’idah:6 provides a more systematic and detailed legal formulation of purification rules, while QS. an-Nisa’:43 emphasizes contextual conditions and concessions in worship. The study concludes that both verses are complementary and together form a comprehensive framework for understanding purification in Islam, both normatively and practically.